Balloon-Assisted Thrombectomy and Intrasinus Urokinase Thrombolysis for Severe Cerebral Venous Sinus Thrombosis - Yang, Jiansheng; Wang, Hongyang; Chen, Yanxing; Qiu, Minjian; Zhang, Baorong; Chen, Zhicai (Frontiers in Neurology, 2021)
Background Current clinical guidelines recommend systemic anticoagulation as the initial treatment for severe cerebral venous sinus thrombosis (CVST). However, anticoagulation alone does not always dissolve large and extensive CVSTs in some patients. Here, we investigated the effectiveness and safety of balloon-assisted thrombectomy and intrasinus urokinase thrombolysis in our retrospective study of a series of 23 CVST patients. Methods We reviewed the clinical, radiological, and outcome data of all patients. Complete recanalization was defined as all the occluded sinuses were recanalized on digital subtraction angiography or Contrast-enhanced magnetic resonance venography. Partial recanalization was defined as the complete recanalization of one sinus but persistent occlusion of other sinuses, or partial recanalization of one or more sinuses. The modified Rankin Scale (mRS) was used to represent the clinical outcome. Results From May 2017 to November 2019, a total of 23 patients were treated with balloon-assisted thrombectomy and intrasinus urokinase thrombolysis. A total of 84 venous sinuses were involved ≥3 sinuses were involved in 20 (87%) patients. Among them, 21 (91%) patients achieved technical success. Complete and partial recanalization were obtained in 17 (81.0%) and 4 (19.0%) patients at 6 months’ follow-up, respectively. All 21 patients had mRS scores of 0 (18) or 1 (3). Conclusions Our case series shows that balloon-assisted thrombectomy combined with intrasinus urokinase thrombolysis and activated partial thromboplastin time-regulated systemic anticoagulation is safe and effective in treating severe CVST.